Towards next-generation visual archives: image, film and discourse. Issue 2 (2nd April 2016) - Bateman, John; Tseng, Chiao-I; Seizov, Ognyan; Jacobs, Arne; Lüdtke, Andree; Müller, Marion G.; Herzog, Otthein
Abstract : The digital turn in visual studies has played a major role in the terminological overlap between 'archive', 'database' and 'corpus', and it has brought about a number of positive developments such as improved accessibility and availability. At the same time, it has also raised important questions pertaining to the materiality, searchability, annotation and analysis of the data at hand. Through a series of theoretical constructs and empirical examples, this paper illustrates the necessity and benefits of interdisciplinary dialogue when tackling the multimodal corpus annotation challenge. The meaningful interrelations between semiotic modes, the combinations between manual and (semi)automated annotation, the seamless integration of coding and annotation schemes which share common logics and the contextual embedding of the presented analyses strongly suggest multimodal document analysis in all its forms will continuously benefit from a corpus-based approach.